Simulation of Kalirejo Road Side Slope based on Altered Andesite Characters, Kulon Progo Regency, Indonesia - Hnin Thandar Phyu; Heru Hendrayana; I Gde Budi Indrawan; Toshitaka Kamai (Journal of Applied Geology, 2021)
ABSTRACT. This study is performed to investigate the characteristics of intrusive andesite rock consisting of Kalirejo Road Side Slope located in Kulon Progo Mountains. The rocks consisting the slope are identified by visual observation of hand specimens in the field, petrographic and X-ray Diffraction (XRD) analyses of the rock samples in the laboratory, upon which genetic rock classification is determined. The altered rock types are determined by the presence of specific minerals identified in the petrographic and XRD analyses. The alteration intensity is examined by comparing the amount of secondary minerals to the primary minerals observed in the petrographic and XRD analyses. The developments of rock weathering are determined in the field GSI classification based on the visual characteristics and in the laboratory-based on the Chemical Index of Alteration (CIA) and engineering properties of the altered rocks. The results show that the rocks typically consisted of 33.2 to 59.2% plagioclase, 1.4 to 5.1% quartz, therefore, are classified as andesite. The presence of halloysite, montmorillonite, and kaolinite as secondary minerals in the altered andesite indicated that the parent andesite rocks have undergone argillic alteration. Meanwhile, the percentages of primary minerals to secondary minerals indicate that the andesite rocks have undergone moderate to high alteration intensity. Based on the visual characteristics, the research area consisted of fresh, slight weathered andesite rocks and complete weathered residual soil. The CIA values of the samples are increased with the increase in rock weathering. Identification of visual characteristics of rock weathering appeared to be in good agreement with those classified based on the CIA and engineering properties analysis results. The uniaxial compressive strength (UCS) of rocks and soils is determined by point load tests. Engineering properties of the residual soils are performed by using ASTM standard procedures. In the lower part of the roadside, slope consists of fresh and slightly weathered andesite rocks, which have relatively high strength and are classified as medium strong rocks. Meanwhile, the upper part of the slope profile contained completely weathered residual soil, which had very low compressive strength, are classified as very weak soil.Keywords:  andesite, argillic alteration, Geological Strength Index (GSI), hydrothermal alteration, roadside slope, weathering